Perencanaan Pengentasan Kemiskinan Ekstrem Di Kabupaten Kotabaru - Oktavianoor, Muhammad Rezki; Oktavianoor, M. Rezki (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
This study aims to analyze the planning of extreme poverty alleviation in Kotabaru Regency using a library research approach based on documents, government publications, and statistical data to understand the root causes of poverty, evaluate policy effectiveness, and analyze the budget allocation amounting to IDR 255,181,642,539 or 7.83% of Kotabaru Regency’s total regional budget for 2024. The findings reveal fluctuating poverty rates influenced by the pandemic and structural challenges, with the poverty rate reaching 4.45% in 2024, although there has been progress in the health and basic infrastructure sectors. The poverty alleviation strategies in the region include reducing the burden of living expenses for the poor, increasing their capacity and income, and eliminating poverty pockets, each aimed at improving conditions in education, employment, health, and basic infrastructure. This research recommends more integrated, up-to-date data-driven policy planning and cross-sectoral synergy to ensure that extreme poverty alleviation programs in Kotabaru Regency are effective and sustainable in supporting the achievement of the 2030 SDGs.